Information systems and technologists and economists - Zhu, Xiaoyi; Kramskoi , D. Ju. (Національний технічний університет "Харківський політехнічний інститут", 2024)
Information systems and technologies in the economy play an important role in ensuring the efficiency, competitiveness and innovation of business. They allow you to collect, process, analyze and use data for making management decisions, planning resources and automating many business processes.
Інформаційні системи та технології в економіці
Keywords: information systems; technology; economics; implementation; automation